Knickpoints and crescentic bedform interactions in submarine channels. Issue 4 (24th May 2021) - Chen, Ye; Parsons, Daniel R.; Simmons, Stephen M.; Williams, Rebecca; Cartigny, Matthieu J. B.; Hughes Clarke, John E.; Stacey, Cooper D.; Hage, Sophie; Talling, Peter J.; Azpiroz‐Zabala, Maria; Clare, Michael A.; Hizzett, Jamie L.; et al.
Abstract: Submarine channels deliver globally important volumes of sediments, nutrients, contaminants and organic carbon into the deep sea. Knickpoints are significant topographic features found within numerous submarine channels, which most likely play an important role in channel evolution and the behaviour of the submarine sediment‐laden flows (turbidity currents) that traverse them. Although prior research has linked supercritical turbidity currents to the formation of both knickpoints and smaller crescentic bedforms, the relationship between flows and the dynamics of these seafloor features remains poorly constrained at field‐scale. This study investigates the distribution, variation and interaction of knickpoints and crescentic bedforms along the 44 km long submarine channel system in Bute Inlet, British Columbia. Wavelet analyses on a series of repeated bathymetric surveys reveal that the floor of the submarine channel is composed of a series of knickpoints that have superimposed, higher‐frequency, crescentic bedforms. Individual knickpoints are separated by hundreds to thousands of metres, with the smaller superimposed crescentic bedforms varying in wavelengths from ca 16 m to ca 128 m through the channel system. Knickpoint migration is driven by the passage of frequent turbidity currents, and acts to redistribute and reorganize the crescentic bedforms. Direct measurements of turbidity currents indicate the seafloor reorganization caused by knickpoint migration can modify the flow field and, in turn, control the location and morphometry of crescentic bedforms. A transect of sediment cores obtained across one of the knickpoints show sand–mud laminations of deposits with higher aggradation rates in regions just downstream of the knickpoint. The interactions between flows, knickpoints and bedforms that are documented here are important because they likely dominate the character of preserved submarine channel‐bed deposits.